2021
DOI: 10.3390/cells10113147
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammasomes by Application of Omega-3 Polyunsaturated Fatty Acids in a Spinal Cord Injury Model

Abstract: Omega-3 polyunsaturated fatty acids (PUFA n3) ameliorate inflammation in different diseases and potentially improve neurological function after neuronal injury. Following spinal cord injury (SCI), inflammatory events result in caspase-1 mediated activation of interleukin-1 beta (IL-1b) and 18. We aim to evaluate the neuroprotective potency of PUFA n3 in suppressing the formation and activation of inflammasomes following SCI. Male Wistar rats were divided into four groups: control, SCI, SCI+PUFA n3, and SCI+Lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown that the unsaturated fatty acid DHA can inhibit NLRP3 and other key proteins of pyroptosis [25]. Unsaturated fatty acids reduce injury-related oxidative stress, decrease microglia/macrophage responses, and improve motor function and bladder function recovery in rats [42]. Following entry into the brain, DHA is esterified into and recycled amongst membrane phospholipids contributing the distribution of DHA in brain phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the unsaturated fatty acid DHA can inhibit NLRP3 and other key proteins of pyroptosis [25]. Unsaturated fatty acids reduce injury-related oxidative stress, decrease microglia/macrophage responses, and improve motor function and bladder function recovery in rats [42]. Following entry into the brain, DHA is esterified into and recycled amongst membrane phospholipids contributing the distribution of DHA in brain phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the spinal cord contains high levels of polyunsaturated fatty acids, which have been shown to be involved in the oxidative stress response following SCI ( Baazm et al, 2021 ). Studies on the regulation of SCI by unsaturated fatty acids such as short-chain fatty acids (SCFA) have been widely reported in recent years ( Filippone et al, 2020 ).…”
Section: The Basic Process Of Ferroptosis and Its Relation To Scimentioning
confidence: 99%
“…Aerobic oxidation, glucose metabolism and lipid metabolism play a crucial role in life activities, all three being interconnected and independent of each other. The role of lipid metabolism in Ferroptosis has been widely reported ( Baazm et al, 2021 ). In contrast, the role of aerobic oxidation and sugar metabolism in Ferroptosis has hardly been reported.…”
Section: The Basic Process Of Ferroptosis and Its Relation To Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Study by Baazm et al [61] states that omega-3 fatty acid supplementation supports neurological function in the event of neuronal injury and suppresses the activity of inflammatory markers.…”
Section: Role Of Omega 3 Fatty Acid In Spinal Cord Injurymentioning
confidence: 99%